International Year of Planet Earth 1. Non-Renewable Resources, Sustainable Development, and Human Evolution — Short Story or Opening Chapter? - Richards, Jeremy (Geoscience Canada, 2008)
SUMMARY Humanity is beginning to grapple with the idea that the Earth is quite a small place when shared by over 6 billion people, and that the physical impact of this number of people on the planet is no longer negligible. In particular, our exponentially increasing use of energy is creating problems both in terms of supply and impact on the environment. Sustainable development has become the buzz word for solving the world’s social, environmental, and ecological problems, but our understanding of what is required for true sustainability is inadequate, and does not recognize the practical limitations we face. We continue to use non-renewable resources, especially fossil fuels, as though there was an unlimited supply, with no consequence to their unbridled consumption. The slow realization by scientists and policy-makers that neither of these things is true has not manifested itself yet in any effective policy formulation on a global scale, and on a local (national, state, or provincial) scale it is largely business as usual. The writer suggests that this is because the human mind has not yet evolved to respond effectively to its relatively novel capacity for reflection on the past and contemplation of the future. We are still stuck with a psyche that is geared to look after only our own interests and those of our immediate family or social group. Our outlook urgently needs to be expanded to embrace the expedient of planning for a secure future for our species as a whole. If we wait for the natural course of evolution to effect this change, we may be too late; but if we positively engage the other human trait of willpower, then perhaps great things are possible. Geoscientists are uniquely equipped with knowledge about the history of our planet and the evolution of the species that have lived on it to inform this debate — we should not keep this knowledge to ourselves, but boldly enter the discussion.